2020
DOI: 10.1111/mms.12695
|View full text |Cite
|
Sign up to set email alerts
|

Mating patterns of dusky dolphins (Lagenorhynchus obscurus) explored using an unmanned aerial vehicle

Abstract: Few studies have explored the mating patterns of freeranging cetaceans, largely because of logistical challenges. We used an unmanned aerial vehicle (UAV) to follow and video-record 25 groups of mating dusky dolphins (Lagenorhynchus obscurus) near the surface of the water and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…For example, we observed dolphins engage in a variety of sociosexual behaviors during feeding and food sharing, and it is unclear how sexual behavior may be related to feeding behavior in this species. Our findings illustrate the power of small aerial drones to track and document the fine‐scale behavior of dolphins (Orbach et al, 2020; Ramos et al, 2018a; Weir et al, 2018). Similar to other marine mammals (e.g., Hartman, van der Harst, & Vilela, 2020; Landeo‐Yauri et al, 2020), individual rough‐toothed dolphins can be identified by their scarring and skin pigmentation patterns.…”
Section: Figuresupporting
confidence: 68%
“…For example, we observed dolphins engage in a variety of sociosexual behaviors during feeding and food sharing, and it is unclear how sexual behavior may be related to feeding behavior in this species. Our findings illustrate the power of small aerial drones to track and document the fine‐scale behavior of dolphins (Orbach et al, 2020; Ramos et al, 2018a; Weir et al, 2018). Similar to other marine mammals (e.g., Hartman, van der Harst, & Vilela, 2020; Landeo‐Yauri et al, 2020), individual rough‐toothed dolphins can be identified by their scarring and skin pigmentation patterns.…”
Section: Figuresupporting
confidence: 68%
“…Among odontocetes, to the authors' knowledge, drones have only been implemented to study a few species of dolphins. Example applications have included identifying dolphin presence and habitat use [137][138][139][140][141][142].…”
Section: Traits Of Dolphinsmentioning
confidence: 99%
“…Promising research approaches may include the use of theodolites (deployed effectively in relation to aquaculture; e.g. Johnston, 2002; Ribeiro et al, 2007; Piwetz et al, 2018) or unoccupied aerial vehicles (Durban et al, 2015; Christiansen et al, 2016; Orbach et al, 2020; Ramos et al, 2021). These vehicles could be used to collect biological samples (e.g.…”
Section: Discussionmentioning
confidence: 99%